Contrasting Gene Expression Profiles of Monocytes and Lymphocytes From Peste-Des-Petits-Ruminants Virus Infected Goats - Wani, Sajad Ahmad; Sahu, Amit Ranjan; Khan, Raja Ishaq Nabi; Pandey, Aruna; Saxena, Shikha; Hosamani, Neelima; Malla, Waseem Akram; Chaudhary, Dheeraj; Kanchan, Sonam; Sah, Vaishali; Rajak, Kaushal Kishor; Muthuchelvan, D.; et al. (Frontiers in Immunology, 2019)
In this study, transcriptome analysis of PPRV infected PBMCs subsets - T helper cells, T cytotoxic cells, monocytes and B lymphocytes was done to delineate their role in host response. PPRV was found to infect lymphocytes and not monocytes. The established receptor for PPRV-SLAM was found downregulated in lymphocytes and non-dysregulated in monocytes. A profound deviation in the global gene expression profile with a large number of unique upregulated genes (893) and downregulated genes (799) was observed in monocytes in comparison to lymphocytes. ISGs - ISG15, Mx1, Mx2, RSAD2, IFIT3, and IFIT5 that play a role in antiviral response and viral sensors – MDA5, LGP2, and RIG1, were found to be upregulated in lymphocytes and downregulated in monocytes. The transcription factors - IRF-7 and STAT-1 that regulate expression of most of the ISGs were found activated in lymphocytes and not in monocytes. Interferon signaling pathway and RIG1 like receptor signaling pathway were found activated in lymphocytes and not in monocytes. This contrast in gene expression profiles and signaling pathways indicated the predominant role of lymphocytes in generating the antiviral response against PPRV in goats, thus, giving us new insights into host response to PPRV.